2018
DOI: 10.1111/gbi.12316
|View full text |Cite
|
Sign up to set email alerts
|

A combined lipidomic and 16S rRNA gene amplicon sequencing approach reveals archaeal sources of intact polar lipids in the stratified Black Sea water column

Abstract: Archaea are important players in marine biogeochemical cycles, and their membrane lipids are useful biomarkers in environmental and geobiological studies. However, many archaeal groups remain uncultured and their lipid composition unknown. Here, we aim to expand the knowledge on archaeal lipid biomarkers and determine the potential sources of those lipids in the water column of the euxinic Black Sea. The archaeal community was evaluated by 16S rRNA gene amplicon sequencing and by quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(113 citation statements)
references
References 113 publications
(257 reference statements)
6
105
2
Order By: Relevance
“…Another filter was directly stored at −80 °C for analysis of the in situ microbial community. Water column samples for nutrient and DNA analysis were collected as described in Sollai et al (2019) and Suominen et al (2020) [ 30 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another filter was directly stored at −80 °C for analysis of the in situ microbial community. Water column samples for nutrient and DNA analysis were collected as described in Sollai et al (2019) and Suominen et al (2020) [ 30 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…10–15 µM [ 26 , 27 ]. ANME-1 have been detected in the Black Sea water column before [ 28 , 29 , 30 , 31 ]. The 13 C-depleted stable carbon isotopic composition of a- and monocyclic biphytanes derived from the characteristic membrane lipids of ANME-1 revealed that these archaea actively consume methane in the water column [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…studies of specific lipid biomarkers and untargeted surveys of the entire POC lipidome (Kharbush et al, 2016;Becker et al, 2018;Sollai et al, 2019).…”
Section: Autochthonous Components Of Poc Lipidsmentioning
confidence: 99%
“…Adding compound-specific isotope analysis in the context of natural isotope abundances (e.g., Schubotz et al, 2009;Pearson et al, 2016) or tracer experiments (e.g., Kellermann et al, 2016) can give further insight into elemental flow within ancient or currently active communities. However, analytical refinements, along with extensive large-scale environmental and laboratory-based surveys, have highlighted the complexity in interpreting the biomarker record solely from a single influencing parameter point of view (Hurley et al, 2016;Sollai et al, 2019). Recent advances have focused on increasing the resolution and sensitivity of lipid analysis.…”
Section: New Lipid Biomarkers and New Uses Of Old Lipid Biomarkersmentioning
confidence: 99%